Hyperhomocysteinaemia aggravates periodontitis by suppressing the Nrf2/HO-1 signalling pathway - Kaiqiang Yang; Yuting Yang; Ting Long; Xiaoxue Wang; Yeke Chen; Chenjiang He; Li Li; Xinbo Yang; Meixiu Jiang; Yichen Hu; Fang Dai; Li Song (Redox Report)
Periodontitis, a common dental illness, causes periodontal tissue inflammation and irreversible bone loss, inevitably resulting in tooth loss. Hyperhomocysteinaemia (HHcy), defined as blood total homocysteine (Hcy) levels greater than 15 µmol/L, is linked to increased cardiovascular disease risk. Mounting evidence indicates a connection between HHcy and periodontitis; however, the underlying processes remain unknown. Herein, we explored the mechanisms by which HHcy exacerbates periodontal tissue inflammation and osteoclast formation. In an animal model of periodontitis treated with HHcy, periodontal attachment loss was aggravated, and both systemic and gingival tissue inflammation levels tended to increase; additionally, antioxidant-related proteins were suppressed and expressed at low levels, whereas oxidative damage-related protein expression increased. In RAW264.7 cells treated with LPS or LPS + Hcy, the LPS + Hcy group presented increased reactive oxygen species (ROS) fluorescence intensity, and Nrf2/HO-1 signalling pathway suppression was associated with inflammatory cytokine (TNF-α) expression. In monocyte osteoclasts treated with Rankl or Rankl + Hcy, the Rankl + Hcy group presented Nrf2/HO-1 signalling pathway suppression, an increase in osteoclast-related proteins (NFATc-1 and CTSK), and a more pronounced osteoclastic phenotype. Therefore, HHcy may exacerbate inflammation severity and osteoclast generation in periodontitis by promoting ROS production and inhibiting the Nrf2/HO-1 signalling pathway.